2013
DOI: 10.1007/s12594-013-0086-7
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Paleo-productivity and Terrigenous Input in the Eastern Arabian Sea during the Past 100 ka

Abstract: A 4.1m long sediment core from the Eastern Arabian Sea (EAS) is studied using multiple geochemical proxies to understand the variation of productivity and terrigenous matter supply during the past 100 ka. The temporal variation in element concentration and fluxes of CaCO3, organic carbon (Corg) and Barium excess (Baexc), together, in general indicate a higher productivity during the cold climate and highest during the Last Glacial Maximum (LGM) in particular. This cold climate-increased productivity coupling m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…The sedimentation rates of the core were estimated by the age of sediment and thickness of sedimentary column. It varies from 0.39 to 7.3 cm/ka with an average w3 cm/ka which are quite similar to that found in a typical continental margin (Van Campo et al, 1982;Clemens and Prell, 1990;Shimmield et al, 1990;Shimmield and Mowbray, 1991;Prell et al, 1992;Sarkar et al, 1993;Sirocko et al, 1996Sirocko et al, , 2000Schulz et al, 1998;von Rad et al, 1999;Thamban et al, 2001;Banakar et al, 2005;Kessarkar and Rao, 2007;Kessarkar et al, 2010;Singh et al, 2011;Ishfaq et al, 2013). From similar sediment accumulation data, various palaeoclimatic inferences have been drawn by many investigators, for instance, determining Table 1 Uncalibrated and calibrated 14 C ages of selected species of Globigerinoides sacculifer size fractions (250e500 mm) in the sediment core SK221/05.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The sedimentation rates of the core were estimated by the age of sediment and thickness of sedimentary column. It varies from 0.39 to 7.3 cm/ka with an average w3 cm/ka which are quite similar to that found in a typical continental margin (Van Campo et al, 1982;Clemens and Prell, 1990;Shimmield et al, 1990;Shimmield and Mowbray, 1991;Prell et al, 1992;Sarkar et al, 1993;Sirocko et al, 1996Sirocko et al, , 2000Schulz et al, 1998;von Rad et al, 1999;Thamban et al, 2001;Banakar et al, 2005;Kessarkar and Rao, 2007;Kessarkar et al, 2010;Singh et al, 2011;Ishfaq et al, 2013). From similar sediment accumulation data, various palaeoclimatic inferences have been drawn by many investigators, for instance, determining Table 1 Uncalibrated and calibrated 14 C ages of selected species of Globigerinoides sacculifer size fractions (250e500 mm) in the sediment core SK221/05.…”
Section: Resultssupporting
confidence: 76%
“…Paleoproductivity in the major part of the western continental margin of India seems to have been controlled by the northeast monsoon, particularly during the last glacial cycles (MIS-2 to MIS-4) as compared to the present interglacial one (MIS-1; Sarkar et al, 1993;Thamban et al, 2001;Banakar et al, 2005;Kessarkar and Rao, 2007;Kessarkar et al, 2010;Singh et al, 2011;Ishfaq et al, 2013). In contrast, the paleoproductivity scenario was found to have been different in the southeastern continental margin during the late Quaternary as there is fragmented and conflicting information (Sarkar et al, 1993(Sarkar et al, , 2000Pattan et al, 2001Pattan et al, , 2003Pattan et al, , 2005Verma and Sudhakar, 2006;Narayana et al, 2009;Das et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the intensified winter winds of the glacial period might have played a significant role in the derivation of fine grained terrigenous material from the continental region and its transportation to the eastern Arabian Sea. Ishfaq et al (2013) recorded less terrigenous input in the eastern Arabian Sea during the past 5 ka. In this study, there is no distinct change observed in the biogenic carbonate during the above period although humidity index shows a minor fall.…”
Section: Paleoenvironmental Implicationsmentioning
confidence: 92%
“…The deposition of sediment in the Arabian Sea can be from a number of sources, i.e., dust originated from Arabia, fluvial detritus from the Indian subcontinent and Somalia (Das et al 2013;Ishfaq et al 2013). Based on the chemical composition of the sediments it is suggested that sediments may also be derived by submarine weathering of Carlsberg Ridge (Shankar et al 1987).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation